2012
DOI: 10.1371/journal.ppat.1002525
|View full text |Cite
|
Sign up to set email alerts
|

Portrait of Candida albicans Adherence Regulators

Abstract: Cell-substrate adherence is a fundamental property of microorganisms that enables them to exist in biofilms. Our study focuses on adherence of the fungal pathogen Candida albicans to one substrate, silicone, that is relevant to device-associated infection. We conducted a mutant screen with a quantitative flow-cell assay to identify thirty transcription factors that are required for adherence. We then combined nanoString gene expression profiling with functional analysis to elucidate relationships among these t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
249
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 207 publications
(272 citation statements)
references
References 46 publications
19
249
0
4
Order By: Relevance
“…Based on their reported GO functions in Candida and Saccharomyces (http://www.candidagenome.org/ and http:// www.yeastgenome.org/), four of these ORFs, SNF5, POL1, orf19.5854.1, and MBP1, were selected for further study. SNF5 (orf19.5871 ) encodes a component of the Swi/Snf chromatin remodeling complex and null mutants display increased MMS sensitivity in Saccharomyces cerevisiae (Chai et al 2005) and anomalous biofilm formation and other pleiotropic defects in C. albicans (Finkel et al 2012). We found that SNF5 homozygous deletants in the CAF2-1 background (TCS1038 and TCS1039) were more sensitive to MMS than its parent, but not as sensitive as CAI4 ( Figure S5A).…”
Section: Candidate Chr3r Genes Responsible For Mms Sensitivitymentioning
confidence: 92%
“…Based on their reported GO functions in Candida and Saccharomyces (http://www.candidagenome.org/ and http:// www.yeastgenome.org/), four of these ORFs, SNF5, POL1, orf19.5854.1, and MBP1, were selected for further study. SNF5 (orf19.5871 ) encodes a component of the Swi/Snf chromatin remodeling complex and null mutants display increased MMS sensitivity in Saccharomyces cerevisiae (Chai et al 2005) and anomalous biofilm formation and other pleiotropic defects in C. albicans (Finkel et al 2012). We found that SNF5 homozygous deletants in the CAF2-1 background (TCS1038 and TCS1039) were more sensitive to MMS than its parent, but not as sensitive as CAI4 ( Figure S5A).…”
Section: Candidate Chr3r Genes Responsible For Mms Sensitivitymentioning
confidence: 92%
“…Profiling can be performed by assessing genome-wide transcription by using microarrays (195,200,(244)(245)(246)(247)(248), NanoString nCounter technology (249,250), and RNA sequencing (RNA-Seq) (197,200) or by using quantitative reverse transcription-PCR (RT-PCR) or Northern blot analysis of a smaller, select group of genes (251). Such comparisons are often made between biofilm preparations and planktonic cultures.…”
Section: Methods For Measuring Biofilms May Be a Source Of Variabilitymentioning
confidence: 99%
“…For this, the following conditions were used: control hyphae, model hyphae, and control hyphae Lack of induction of these three genes may be due to the fact that these cells were cultured in a mammalian culture medium containing glucose. These results are in agreement with a previous report, which showed that glucose did not significantly induce the expression of GlcNAc catabolism genes [14]. Furthermore, our results showed that the expression of all four genes (NGT1, DAC1, HXK1, and NAG1) genes involved in GlcNAc catabolism were all significantly upregulated in model hyphae and upon GlcNAc induction (Figure 4).…”
Section: Expression Analysis Of Genes Involved In Glcnac Metabolismsupporting
confidence: 93%
“…An important initial step during pathogenesis is adhesion. A large set of adhesins and a complex regulatory machinery have already been identified [14]. After adhesion and hyphal induction, penetration is facilitated by a set of secreted aspartic proteases [15].…”
Section: Pathogenesis and Immune Defensementioning
confidence: 99%